In Vitro Initiation, Regeneration, and Characterization of Plants Derived from Mature Tetraploid Floral Explants of Date Palm (Phoenix dactylifera L.) - Ahmed Othmani; Amel Sellemi; Monia Jemni; Karim Kadri; Leen Leus; Stefaan P. O. Werbrouck (Horticulturae)
A stable tetraploid date palm mutant with the potential for increased fruit size was recovered from a sectorial di-tetraploid chimera via the in vitro culture of flower explants. Callus was induced using 2,4-D, followed by shoot regeneration on a medium containing NAA and BAP and rooting with IBA. Regenerated plantlets, confirmed as tetraploid via flow cytometry, were acclimatized and grown for six years. The leaves of tetraploids exhibited significantly wider petiole bases, thicker rachis and spines, broader leaflets, and a more intense green leaf color compared to diploids. However, leaf length, spine count, and overall leaf number were reduced. This is the first report of successful tetraploid recovery from a chimeric date palm, demonstrating the potential of this technique to generate novel germplasm and highlighting the phenotypic differences associated with tetraploidy in this species.